Recent Advances in Zebrafish Researches - Bozkurt, Yusuf (IntechOpen, 2018)
Model organisms have been used in various disciplines in order to understand different mechanisms underlying the problems. From this point of view, the zebrafish has become a favorite model organism in different scientific research fields in recent years because of its rapid embryonic development, transparency of its embryos, and its large number of offspring along with several other advantages. Recent Advances in Zebrafish Researches demonstrates the role and the function of zebrafish in different research fields and totally includes 11 chapters, which have been written by the expert researches in their fields. With this book, every researcher will better understand different mechanisms underlying the problems at different disciplines using zebrafish as model organism.